A review on cell balancing techniques and their complexity levels - TUNABOYLU, BAHADIR (My University, 2022)
With the increasing adoption of battery-based energy storage systems, especially in areas such as e-mobility and on- and off-grid energy storage applications, techniques to manage these batteries are being developed to address various application-related challenges. Battery Management Systems (BMS) are used to provide reliable protection for the connected battery pack. One of the tasks of a BMS is Cell Balancing (CB), in which the BMS tries to ensure that each individual cell or cell module has the same voltage level during charging and discharging operations. This task can become critical in applications involving Li-ion batteries, due to their sensitivity to being overcharged or deeply discharged. The complexity of a CB technique, and thus its implementation cost, depends on the battery chemistry and the sensitivity of the application. Thus, different designs with different complexity levels are being developed to address the balancing issue. This paper explores the CB techniques found in the literature in the past 20 years and categorizes them based on their complexity level. Operational and feature comparisons were carried out between the different CB designs.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; Endüstri Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; Industrial Engineering; Engineering and Technology; MÜHENDİSLİK, ENDÜSTRİYEL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); YÖNETİM; Ekonomi ve İş; Sosyal Bilimler (SOC); ENGINEERING, INDUSTRIAL; ENGINEERING; Engineering, Computing & Technology (ENG); MANAGEMENT; ECONOMICS & BUSINESS; Social Sciences (SOC); General Decision Sciences; Decision Sciences (miscellaneous); General Engineering; Engineering (miscellaneous); Social Sciences & Humanities; Physical Sciences; Battery management system (BMS); Cell balancing; Batteries; Energy storage; BATTERY-MANAGEMENT-SYSTEM; ENERGY-STORAGE; EQUALIZATION; CIRCUIT